FEATURES PERITONEAL FACTORS IN EXTERNAL GENITAL ENDOMETRIOSIS - S. V. Barinov; E. I. Novikova; D. G. Novikov; A. V. Indutny; L. N. Vasilenko (Акушерство, гинекология и репродукция, 2016)
Objective. To determine the diagnostic value of the concentration of cytokines and growth factors contained in the biological fluids of patients with external genital endometriosis (EGE). Materials and Methods. Clinical data were evaluated and the concentration of IL-1 β, IL-6, IL-8, IL-10, α 2-macroglobulin, vascular endothelial growth factor (VEGF) in 18 patients with EGE. Results. Significant differences were found between the concentration of the studied markers in venous blood and peritoneal fluid (PF). We found a relationship between pain of patients with EGE and the concentration of IL-10 (r=0,480 p=0,135), VEGF (r=0,478 p=0,277) and α 2-macroglobulin in the PF (r=0,554, p=0,049). The dependence between the concentration of IL-6 in the PF and the prevalence of pathological process in EGE (r=0,560, p=0,005). We found significant increase of the concentration VEGF in the PF of patients with EG compared with the control group. Conclusion. The data obtained allow the use of research concentration of markers in the peritoneal fluid of patients with EGE to predict the future course of the disease.